Metode Ketenangan Jiwa: Suatu Perbandingan antara al-Ghazâlî dan Sigmund Freud - Syakur, Abd (Program Pascasarjana UIN Sunan Ampel Surabaya, 2007)
Al-Ghazâlî and Freud are both concerned with the idea soul âand within itthenotion of spiritual tranquility. They both argue that soul has qualities such as health,sickness, tranquility, worriness, and so on, which need to be managed and organized.However, the paradigm within which they speak of this notion is sharply different. For al-Ghazâlî, the nature of soul is purity. Hence it tends to resort to virtue and avoid vice. Al-Ghazâlî reckons that they are degrees of soul. But that which is tranquil is the highestdegree of soul. This soul is what he âborrowing the Qurâan- calls al-Nafs al-Mutmaâinnah(the tranquil soul). For Freud on the other hand, soul is an abstraction of manâspsychological and physical system. It is impulsive, and tends to seek material and physicalsatisfaction through sexual pleasure among others. Man in his view is a sexual being. Hespeaks of the structure of soul as having three categories, namely Id, Ego and Super-ego.It is Id -meaning lust- that dominates oneâs soul. Man will acquire tranquility once he âbymeans of his Ego and Super-ego- satisfied his Id. Conversely, a failure to satisfy Id willresult in a psychological disorder. Hence the sharp contrast between al-Ghazâlî andFreud. And it is about this contrast that this paper is concerned.